Perlindungan Benda Sitaan Negara dan Barang Rampasan Negara dalam Proses Peradilan Pidana (Lex Jurnalica, 2012)
AbstractThe remedies in respect of an offense that often typically received less attention is the protection of objects confiscated or evidence of a criminal process. Of a series of criminal justice process from the level of investigation, prosecution and up to the judge's decision must include evidence that the defendant used in committing a crime. In order to evidence and secure the spoils of the State and the integrity required of a special institution to save the State Foreclosure Home Storage Objects (RUPBASAN) any institution authorized Act - legislation to implement the storage of confiscated items and loot the country. Problems in this paper is how the shape of objects confiscated and the protection of the State of booty and how the process of execution against the State confiscated objects, whereas the purpose of this paper is intended to answer questions - questions contained in the subject matter is to determine the protection of objects confiscated and State booty and to learn about the process of execution of confiscated items and loot the State. This study uses a normative juridical approach of juridical and empirical use of primary data, secondary data and tertiary data. Some fakor lack of protection for confiscated items and loot the State due to storage, research, and securing a less responsible. Efforts to protect objects of booty seized and the State in the criminal justice process is important because it has the function to strengthen the confidence of judges in assessing the truth of the material and formal errors also complete the accused and the evidence that has been defined by the Regulation.Keywords: the state, country confiscated objects, criminal justice processÂ AbstrakTindak pidana yang kurang mendapat perhatian adalah perlindungan benda sitaan atau bukti dari proses pidana. Dari serangkaian proses peradilan pidana dari tingkat penyidikan, penuntutan dan sampai putusan hakim harus menyertakan bukti bahwa terdakwa digunakan dalam melakukan kejahatan. Dalam rangka untuk mengamankan bukti dan barang rampasan Negara dan integritas diperlukan suatu lembaga khusus untuk menyimpan Negara Objects Foreclosure Home Penyimpanan (RUPBASAN) instansi yang berwenang Act - undang-undang untuk melaksanakan penyimpanan barang sitaan dan menjarah negara. Permasalahan dalam makalah ini adalah bagaimana bentuk benda disita dan perlindungan dari Negara jarahan dan bagaimana proses eksekusi terhadap benda disita negara, sedangkan tujuan dari makalah ini dimaksudkan untuk menjawab pertanyaan - pertanyaan yang terkandung dalam materi pelajaran yang untuk menentukan perlindungan benda disita dan rampasan Negara dan belajar tentang proses eksekusi barang sitaan dan menjarah negara. Penelitian ini menggunakan pendekatan yuridis normatif penggunaan yuridis dan empiris dari data primer, data sekunder dan data tersier. Beberapa fakor kurangnya perlindungan untuk barang-barang disita dan menjarah Negara karena penyimpanan, penelitian, dan mengamankan kurang bertanggung jawab. Upaya untuk melindungi obyek jarahan disita dan Negara dalam proses peradilan pidana adalah penting karena memiliki fungsi untuk memperkuat keyakinan hakim dalam menilai kebenaran material dan kesalahan formal juga menyelesaikan terdakwa dan bukti-bukti yang telah didefinisikan oleh Peraturan tersebut.Kata kunci: Â negara, sitaan negara, peradilan pidana